Strategi digital marketing Jasa Photography (analisis akun instagram@bingkaicerita.Photography - Rahmad Afandy (Fak. Ilmu Sosial dan Humaniora Universitas Islam Negeri Sunan Kalijaga, 2023)
et,1/isr,c.1